2012
DOI: 10.4103/0019-557x.96977
|View full text |Cite
|
Sign up to set email alerts
|

Risk for oral cancer associated to smoking, smokeless and oral dip products

Abstract: Oral cancer is one of the most common life threatening diseases in India. Tobacco and alcohol are considered to be the most risk factors for oral cancer. This study was conducted to investigate the association of tobacco and poly-ingredient oral dip products with oral cancer. A case-control study of 350 cases and 350 controls, over a period of 19 months, between February 2005 and September 2006 was carried out in Pune, India. The self-reported information about the consumption of tobacco, poly-ingredient oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 0 publications
7
35
1
1
Order By: Relevance
“…A study by Lin et al (2011) supported to our findings. Some previous studies reported that a great risk of oral cancer in consumers who chewing tobacco and kept in the mouth for different duration of time, depending on the personal habits (Muwonge et al, 2008;Madani et al, 2012). Contradictory results also have been obtained in other studies.…”
Section: Discussionmentioning
confidence: 72%
“…A study by Lin et al (2011) supported to our findings. Some previous studies reported that a great risk of oral cancer in consumers who chewing tobacco and kept in the mouth for different duration of time, depending on the personal habits (Muwonge et al, 2008;Madani et al, 2012). Contradictory results also have been obtained in other studies.…”
Section: Discussionmentioning
confidence: 72%
“…Since a pioneer study by Wynder & Bross (1957), the role of tobacco consumption in oral carcinogenesis has been consistently demonstrated by numerous studies, including huge cohort studies (Znaor et al, 2003;Muwonge et al, 2008;Rosenquist, 2008;Javalekshmi et al, 2011;Madani et al, 2012). Moreover, findings from a nationally representative sample in India which have among the highest prevalence of oral cancer in the world showed that tobacco-related cancers accounted for 42% and 18.3% of male and female deaths respectively, where there were twice as many deaths among oral cancer as compared to lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…of bidis and cigarettes or as smokeless forms like tobacco chewing or mishri (tobacco used as tooth cleanser) is the main etiological agent of oral cancer. 8 Studies have shown that the usage of tobacco in various forms is mounting at the rate of 2 to 3% yearly, and it is expected to cause about 13% of deaths in India by 2020. 9 Oral cavity has rich blood supply and lymphatic drainage, therefore the likelihood of cervical metastases of OSCC is very high making it a life-threatening disease.…”
Section: Resultsmentioning
confidence: 99%